The Virtue of "Selling Out": Compromise as a Moral Transaction - Yeager, Diane M. (Journal of the Society of Christian Ethics, 2017)
In this rehabilitation of the relational transaction of compromising, we follow Paul Ricoeur in arguing that at the intersection of diverse orders of value, compromising rises to the level of a moral duty. Thus, an ethics of compromise, rooted in recognition theory, provides a virtuous means of moral engagement with otherness in the context of pluralism. Virtue theory needs to move in an interactive direction by (a) enlisting moral epistemology, for a shift in focus from the individual agent (personal integrity) to the interaction of agents (social cooperation); (b) attending to the political theorists and sociologists who ground meaningful compromise in mutual recognition; and (c) tailoring such recognition to bounded human capacities for rationality and empathy, via "psychological realism"all in service of attenuating the discomfort and even moral pain that agents may feel when called upon to compromise.